Kendala Penerapan Pembelajaran Daring pada Mahasiswa di Fakultas Keguruan dan Ilmu Pendidikan Universitas Khairun - Eko Purnomo; Rasmi Hi Panu; Wawan S. Nadra (EDUKASI, 2023)
The implementation of online learning was implemented suddenly due to the Covid-19 pandemic that hit in 2019, online learning policies are a temporary solution to stop the spread of Covid-19. However, this policy has had a big impact on the world of education, various problems arise from the factor of implementing the policy. This study aims to examine the obstacles to the implementation of online learning experienced by FKIP students, Unkhair. The method used in this study is a descriptive quantitative approach. Data collection through surveys. The instrument used is an electronic questionnaire via google form. The questionnaire used is a closed questionnaire and an open questionnaire. The correspondents of this study were FKIP Unkhair students as many as 150 correspondents who were representatives of 7 study programs. Based on the results of the research analysis, it can be concluded that there are 4 points of obstacles faced by FKIP students during online learning, namely limited internet quota, inadequate internet network, low understanding of IT and limited infrastructure. However, these obstacles can be anticipated through serious online learning designs by considering the convenience of learning, the readiness factors of lecturers and students and the availability of supporting facilities. In conclusion, there are 4 obstacles to implementing online learning policies. To overcome them, the involvement of all parties is required to design high-quality online learning.